Electron Backscatter Diffraction and Transmission Kikuchi Diffraction Analysis of an Austenitic Stainless Steel Subjected to Surface Mechanical Attrition Treatment and Plasma Nitriding. (3rd July 2015) - Proust, Gwénaëlle; Retraint, Delphine; Chemkhi, Mahdi; Roos, Arjen; Demangel, Clemence
Abstract: Austenitic 316L stainless steel can be used for orthopedic implants due to its biocompatibility and high corrosion resistance. Its range of applications in this field could be broadened by improving its wear and friction properties. Surface properties can be modified through surface hardening treatments. The effects of such treatments on the microstructure of the alloy were investigated here. Surface Mechanical Attrition Treatment (SMAT) is a surface treatment that enhances mechanical properties of the material surface by creating a thin nanocrystalline layer. After SMAT, some specimens underwent a plasma nitriding process to further enhance their surface properties. Using electron backscatter diffraction, transmission Kikuchi diffraction, energy dispersive spectroscopy, and transmission electron microscopy, the microstructural evolution of the stainless steel after these different surface treatments was characterized. Microstructural features investigated include thickness of the nanocrystalline layer, size of the grains within the nanocrystalline layer, and depth of diffusion of nitrogen atoms within the material.